Hubungan Serotinus dengan Kejadian Asfiksia Bayi Baru Lahir di Rumah Sakit Umum Daerah Kota Kendari Tahun 2015 - Elyasari, Elyasari; Listi, Listi (Poltekkes Kemenkes Kendari, 2018)
Newborn asphyxia is a condition where the baby is born can not immediately breathe spontaneously and regularly after birth (Wiknjosastro, 2007). AKB in Kendari City in 2014 as many as 26 people out of 6,228 newborns with the incidence of asphyxia in newborns in Kendari City General Hospital in 2015 as many as 78 people out of 950 newborns and the number of infants experiencing serotinus as many as 40 babies (Medical Record of Kendari City Hospital, 2015). Objective to determine the relationship between serotinus and the incidence of asphyxia in newborns at the Kendari Regional General Hospital in 2015. The type of research used was analytic with the design of Case-Control. The sampling technique was purposive sampling, in which all asphyxial infants were taken as a case. The systematic sampling technique was random sampling, where all non-asphyxial infants were numbered, and from 872 non-asphyxial infants divided by the number of controls taken 872: 78 = 11.2, so that the sample for control is a multiple of 11. Based on data analysis obtained results, namely from 78 infants with asphyxia there were 10 people (12.8%) babies born with serotinus. The value of X2counts 5,778> X2 table 3,841 so that H0 is rejected and Ha is accepted with OR = 5.588 (p= 0.032). There is a relationship between serotinus and the incidence of asphyxia in newborns in Kendari Regional General Hospital in 2015.